Training in the Utilization of Artificial Intelligence - Based Digital Media at SMP Muhammadiyah PK Kottabarat Surakarta - Sholihati, Rubiatun Nurush; Maksum, Muh. Nur Rochim; Shohib, Muhammad Wildan (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to provide training for teachers at SMP Muhammadiyah Program Khusus Kottabarat Surakarta on the ethical and productive use of artificial intelligence (AI) in teaching and learning activities. Methodology: The study employed a Participatory Action Research (PAR) approach, consisting of three stages: pre-operational (needs identification), operational (training and mentoring), and post-operational (reflection and follow-up). Results: The training involved 32 teachers and 6 members of the Koddekido team. Through these activities, teachers successfully practiced coding and independently developed interactive quizzes with the assistance of AI, ranging from general information processing to the design of instructional media. These results indicate an improvement in teachers’ capacity to design more effective and efficient learning media. Applications/Originality/Value: The impact of this program is reflected not only in the participants’ positive responses to the training but also in a paradigm shift in teachers’ perceptions of AI as a creative and collaborative support tool in the educational process. In addition to the training, the Koddekido team provided guidance on the ethical use of AI in developing instructional materials to ensure responsible utilization and adherence to principles of originality.